2022
DOI: 10.1507/endocrj.ej21-0590
|View full text |Cite
|
Sign up to set email alerts
|

Double water-clear cell parathyroid adenoma: a case report and literature review

Abstract: Water-clear cell parathyroid adenoma is an uncommon cause of primary hyperparathyroidism. Herein, we report an interesting case of a 56-year-old man who presented with weight loss, bone pain, fatigue, and a palpable right neck mass. Laboratory tests indicated hypercalcemia, elevated parathyroid hormone (PTH) levels, and normal thyroid function. Further examinations detected osteoporosis and kidney stones. The ultrasound of neck revealed bilateral extrathyroidal tumors, which were sestamibi-avid. The patient un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…"Painful bones, renal stones, abdominal groans, and psychic moans" are terms that have been used to describe the spectrum of symptoms. Biochemically, the most common manifestation of primary hyperparathyroidism is an increase in the level of serum ionized calcium [ 6 ]. The serum abnormalities may lead to nephrolithiasis, gastrointestinal disturbances such as constipation, and neuromuscular complaints manifesting as weakness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…"Painful bones, renal stones, abdominal groans, and psychic moans" are terms that have been used to describe the spectrum of symptoms. Biochemically, the most common manifestation of primary hyperparathyroidism is an increase in the level of serum ionized calcium [ 6 ]. The serum abnormalities may lead to nephrolithiasis, gastrointestinal disturbances such as constipation, and neuromuscular complaints manifesting as weakness and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…The WCC adenoma is an extremely rare subtype of parathyroid adenoma. A recent literature review claims that only 37 cases have been reported in the English literature between 1985 and 1981, with most occurring in middle-aged women [ 6 ]. WCCs are not considered part of normal parathyroid architecture.…”
Section: Discussionmentioning
confidence: 99%